BIOM-12. CIRCULATING TUMOR DNA IN ADULTS WITH GLIOMA: A SYSTEMATIC REVIEW AND META-ANALYSIS OF BIOMARKER SENSITIVITY. (9th November 2020) - McMahon, James; Studer, Matthew; Ulrich, Bryan; Pradilla, Gustavo
Abstract: BACKGROUND: Circulating tumor DNA (ctDNA) has emerged as a promising non-invasive biomarker to capture tumor genetics in patients with primary brain tumors. Research into its clinical utility, however, has not been standardized, as performance statistics of ctDNA remain undefined and optimal ctDNA assay and biospecimen sources for its evaluation have not been conclusively identified. We sought to determine a pooled sensitivity of the detection ctDNA in both CSF in plasma when compared to detecting the same mutant DNA in tumor tissue of gliomas. We then sought to compare ctDNA sensitivity between these two reservoirs, as well as between individual WHO grades of glioma. METHODS: Following PRISMA guidelines, systematic review and meta-analysis was performed using published studies that assessed circulating tumor DNA in either plasma or CSF among adult patients with histopathology-confirmed glioma. Weighting of individual studies was conducted to reach an overall pooled sensitivity of ctDNA detection in both CSF and plasma. Chi-squared tests of independence were performed to compare overall sensitivity of ctDNA in CSF versus plasma, as well as to estimate the sensitivity of ctDNA for each WHO grade of glioma. RESULTS: The overall reported sensitivity of ctDNA in CSF was found to be 77.4%, significantly higher than the 38.8% sensitivity in plasma (p< 0.0001). Sensitivity was significantly higher for high grade (82.8%) than low grade (60.5%) tumors in CSF (p=0.0023), and sensitivity was found to sequentially increase with increasing WHO grade. Qualitative analysis revealed evidence of greater sensitivity among single-allele PCR or small targeted next generation sequencing (NGS) panels, and increased sensitivity among larger tumors and those in proximity to cisternal or ventricular CSF. CONCLUSION: Circulating tumor DNA is potentially a highly sensitive non-invasive biomarker among adults with gliomas. To maximize its sensitivity, CSF should be studied with targeted genetic analysis platforms, particularly in suspected high-grade gliomas.